Novel Non-Thermal Synthesis and Characterization of Mesoporous Sn(IV) Silicates - SEPEHRIAN, H.; KHANCHI, A.R.; ROFOUEI, M.K.; WAQIF HUSAIN, S. (Asian Journal of Chemistry, 2010)
Sn(IV) incorporated mesoporous molecular sieves with Si/Sn ratios of 10, 20, 40, and 80 have been successfully synthesized under non-thermal conditions at ambient temperature. They have been characterized by means of X-ray diffraction, nitrogen adsorption isotherms, FT-IR spectroscopy, transmission electron microscopy and thermogravimetry analysis. Nitrogen adsorption data and XRD patterns confirmed that, the framework, high surface area and uniform pore size distribution are maintained in the crystallized sample with Si/Sn ratios of 40 and 80.